Interest Group Support and Electoral Success in the Swiss Elections of 2015. A Candidate Survey Analysis. Issue 4 (10th December 2018) - Lutz, Georg; Mach, André; Primavesi, Riccardo
Abstract: Politicians, parties and interest groups are strongly interlinked in Switzerland. Most studies focus on the interest group influence during parliamentary legislative processes. This article fills a gap by focusing on a question that was largely ignored so far: the impact of interest group support on electoral success of candidates. We collected information on the magnitude and nature of self‐reported relations between individual candidates and many interest groups in the 2015 Swiss national election. This new and unique data set allows us to explore the varying impact of specific interest group types on candidates electoral success. Being endorsed by many interest group and occupying leading positions are positively correlated with larger shares of preference votes, while financial contribution show no significant impact. There is, however, variation how endorsements by and leading positions at interest group matter for candidates from different parties depending on the type of interest group.